2010
DOI: 10.1016/j.bbalip.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-V associates with intrahepatic lipid droplets and influences triglyceride accumulation

Abstract: Apolipoprotein A-V (apoA-V), secreted solely by the liver, is a low abundance protein that strongly influences plasma triglyceride (TG) levels. In vitro, in transfected hepatoma cell lines apoA-V is largely retained within the cell in association with cytosolic lipid droplets (LD). To evaluate if this is true in vivo, in the present study the amount of apoA-V in the plasma compartment versus liver tissue was determined in APOA5 transgenic (Tg) mice. The majority of total apoA-V (~80%) was in the plasma compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…Treatment of stably transfected McA-RH7777 hepatoma cells with oleate, which increased intracellular TG accumulation, caused a dramatic inhibition of apoA-V secretion and a reciprocal increase in intracellular apoA-V. Fluorescence confocal microscopy established that this was due to the association of apoA-V with the surface of cytosolic lipid droplets, as observed previously ( 23,24,32 ). Hence, it appears that hepatic TG synthesis or accumulation may drive a dynamic competition between apoA-V secretion and lipid droplet association.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Treatment of stably transfected McA-RH7777 hepatoma cells with oleate, which increased intracellular TG accumulation, caused a dramatic inhibition of apoA-V secretion and a reciprocal increase in intracellular apoA-V. Fluorescence confocal microscopy established that this was due to the association of apoA-V with the surface of cytosolic lipid droplets, as observed previously ( 23,24,32 ). Hence, it appears that hepatic TG synthesis or accumulation may drive a dynamic competition between apoA-V secretion and lipid droplet association.…”
Section: Discussionmentioning
confidence: 48%
“…Shu et al ( 32 ) observed that both the hepatic TG content and the apoA-V lipid droplet association were increased in human apoA-V transgenic mice, whereas inactivation of the mouse apoA-V gene had little effect. Although the impact on plasma TG was not examined in that study, Pamir et al ( 45 ) found that when human apoA-V transgenic mice were fed a high-fat and high-sucrose diet, fasting plasma TG levels fell instead of increasing, suggesting that apoA-V gene expression had inhibited diet-induced hepatic VLDL-TG secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this elevation was associated with elevated plasma and VLDL triglyceride concentrations. These observations suggest that moderate CKD could be associated with dysregulated apoA-V metabolism, which may have an impact on the metabolism of TRL ( 38,39 ). Future studies using VLDL triglyceride kinetics, coupled with cellular studies are warranted to better understand the role of apoA-V in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis showed that apoA-V is very hydrophobic and predominately lipid-bound (3,72), associating with plasma high-density lipoprotein, VLDL, and chylomicrons (47). What potentially made apoA-V elusive in its discovery was its low plasma concentration, a range of 114 -258 ng/ml in normolipemic individuals (26,47,59,64). The interesting question is how can an apolipoprotein of such low plasma concentration affect plasma TG so dramatically?…”
mentioning
confidence: 99%